Pengaruh Brand Familiarity Dan Perceived Quality Terhadap Brand Credibility (Studi Kasus Merek Solventum) di Kota Medan - Lidya Vanessa; Lingga Yuliana (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the effect of Brand Familiarity and Perceived Quality on Brand Credibility. A quantitative descriptive approach was employed, using purposive sampling as the sampling technique. The respondents in this study were dentists who use the Solventum brand. The data used were primary data collected from 207 respondents domiciled in Medan City. Data collection was conducted through the distribution of questionnaires using Google Forms on July 12, 2025. Data analysis was performed using the Statistical Package for the Social Sciences (SPSS) with the assistance of IBM SPSS Statistics version 27.0.1. The results indicate that Brand Familiarity does not have a significant effect on Brand Credibility, therefore the first hypothesis is not supported. Meanwhile, Perceived Quality has a significant effect on Brand Credibility, supporting the second hypothesis of this study.